Pharmacokinetic Profile of Kaurenoic Acid after Oral Administration of Araliae Continentalis Radix Extract Powder to Humans - Eun-Jeong Choi; Go-Wun Choi; Seung-Jeong Yang; Yong-Bok Lee; Hea-Young Cho (MDPI AG, 2018)
The objective of this study was to characterize pharmacokinetics (PKs) of kaurenoic acid (KAU) after administration of the clinical usual dose of Araliae Continentalis Radix extract powder to Korean subjects for the first time and evaluate the mechanism of its absorption in vitro. A simple, sensitive, and selective analytical method was developed for the detection of KAU in human plasma. Concentrations of KAU were quantified by ultra-performance liquid chromatography tandem mass spectrometry after simple liquid⁻liquid extraction. This pharmacokinetic model of KAU was best described by a two-compartment model with first-order absorption. To identify efflux transporters involved in the absorption of KAU, a Caco-2 monolayer model was used. Estimated PK parameters were: systemic clearance, 23.89 L/h; inter-compartmental clearance, 15.55 L/h; rate constant for absorption, 1.72 h−1; volume of distribution of the central compartment, 24.44 L; and volume of distribution of the peripheral compartment, 64.05 L. Results from Caco-2 bidirectional transport study suggested that KAU was a potential substrate of efflux transporters. In summary, PKs of KAU were successfully characterized after administration of a usual dose of Araliae continentalis Radix extract powder in human with the newly developed bioanalytical method and the mechanism of absorption of KAU was identified clearly.